(untitled) (Annals of Bangladesh Agriculture, 2026)
Mango cultivation is a vital source of agricultural income and a key contributor to rural livelihoods in Bangladesh. To better understand the economic potential of this sector, data were collected through a structured interview schedule with 240 commercial mango growers from the central mango producing region of Rajshahi, Bangladesh, during the 2023-2024 season. A stratified random sampling method was used to account for differences in farm size and resource use. The socioeconomic status of the farmers was profiled using descriptive statistics, while costs and revenues were estimated through enterprise budgeting techniques. Factors influencing mango income were identified using multiple linear regression. The findings reveal that most farmers are middle-aged, manage an average of 1.45 hectares of orchard land, and possess a moderate level of education, with limited access to training and credit facilities. Production primarily involves grafted trees of BARI Aam-3, Himsagar, and Langra varieties, with basin irrigation and pesticide use being standard practices. Despite the high costs of pesticides and hired labor, the average yield was 20.54 tons per hectare, resulting in a profit-to-cost ratio of 2.03, which confirms mango farming as a profitable venture. Regression analysis reveals that larger landholdings, land ownership, and participation in training significantly enhance mango income, whereas education and farming experience have notable adverse effects on mango income. Other factors such as age, household size, and access to credit were not found to be statistically significant. These insights underscore the importance of expanding training programs, enhancing land-use efficiency, and developing targeted interventions for older and resource-constrained households to improve the profitability and sustainability of mango cultivation. Ann. Bangladesh Agric. 29(2): 219-237